2017
DOI: 10.1186/s12995-017-0164-7
|View full text |Cite
|
Sign up to set email alerts
|

An index to characterize female career promotion in academic medicine

Abstract: BackgroundImbalances in female career promotion are a key factor of gender disparities at the workplace. They may lead to stress and stress-related diseases including burnout, depression or cardiovascular diseases. Since this problem cannot be generalized and varies between different fields, new approaches are needed to assess and describe the magnitude of the problem in single fields of work.MethodsTo construct a new index, operating figures of female and male medical students were collected for Germany in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…A steady tenure track and an increased number of publications are vital for academic promotions, but our study depicts that female faculty members have significantly lesser publications than male members. The results are in alignment with studies done in other countries (Buckley et al, 2000;Brüggmann & Groneberg, 2017). In 2017, it was indicated that women are less likely to become Professors in Cardiology (Carne & Merz, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…A steady tenure track and an increased number of publications are vital for academic promotions, but our study depicts that female faculty members have significantly lesser publications than male members. The results are in alignment with studies done in other countries (Buckley et al, 2000;Brüggmann & Groneberg, 2017). In 2017, it was indicated that women are less likely to become Professors in Cardiology (Carne & Merz, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…This was not studied in our study and may be an opportunity for future research. Females were the majority in our study and this has been the status for several years in medicine in the western world, they also are more likely to use electronic devices to study compared with males …”
Section: Discussionmentioning
confidence: 87%
“…Moreover, in the academic environment, female scholars encounter many more difficulties than their male counterparts and this may enhance their appreciation of positive collaborative networks. Numerous studies of female scholars have shown that they have less support, face greater professional isolation and slower rates of promotion, and are more likely to leave the academia before gaining tenure than their male counterparts (Wasburn, 2007; Baker, 2010; Brüggmann and Groneberg, 2017; Oleschuk, 2020). In order to overcome these challenges, some female scholars develop exceptional communication skills and make good use of their extensive connections.…”
Section: Resultsmentioning
confidence: 99%